Freezing Tolerance of Field‐ and Growth Chamber–Acclimated Zoysiagrass Hybrids. Issue 1 (19th October 2017) - Wu, Y.; Chandra, A.; Genovesi, A. D.; Meeks, M.
Abstract : The objective of this study was to test the freezing tolerance of a medium‐fine textured ecotype (DALZ 1301) of zoysiagrass ( Zoysia spp.) and six fine‐textured interspecific hybrids (DALZ 1304–1309) derived from crosses between Z. minima (Colenso) Zoltov. or Z. pauciflora (Mez.) and Z. matrella (L.) Merr. after cold acclimation under field (FE‐1 and FE‐2) and controlled‐environment conditions (GC‐1 and GC‐2) in 2014 and 2015. Following acclimation, samples were subjected to six freezing treatments (–3, –5, –7, –9, –11, and –13°C) for 1 h, thawed, and placed under optimum greenhouse conditions for recovery. Greenup was visually rated on a 1 to 9 scale (1 = brown; 9 = completely green; 5 = acceptable) at 5 wk. Lethal temperatures (LT50 ) for each genotype were determined by nonlinear regression. Mean LT50 for field‐acclimated samples ranged from –5.5°C (DALZ 1307) to –9.3°C (Meyer). Mean LT50 for controlled‐acclimation samples ranged from –1.6°C (DALZ 1304) to –9.9°C (Meyer) in GC‐1 and from –4.8°C (DALZ 1304) to –9.4°C (Meyer) for GC‐2. The LT50 of DALZ 1301 and Meyer were statistically similar, but interspecific hybrids were less freeze tolerant than Meyer. Results suggest a limited potential of Z. minima, Z. pauciflora, and Z. matrella lines to impart freezing tolerance. Additionally, high correlations (R 2 = 0.718–0.767) of lethal temperatures with field and controlled acclimation experiments, suggest controlled‐environment acclimation is suitable for testing freezing tolerance in zoysia.